Calibration of Underwater Sound Transducers - Sastry, H.R.S. (Defence Science Journal, 2014)
The techniques of calibration of underwater sound transducers for farfield, near-field and closed environment conditions are reviewed in this paper .The design of acoustic calibration tank is mentioned. The facilities available at Naval Physical & Oceanographic Laboratory, Cochin for calibration of transducers are also listed.